A novel, simplified method to prepare and preserve freeze-dried mouse sperm in plastic microtubes - Li Ly YANG; Daiyu ITO; Natsuki USHIGOME; Sayaka WAKAYAMA; Masatoshi OOGA; Teruhiko WAKAYAMA (The Society for Reproduction and Development, 2023)
Although freeze-drying sperm can save space, reduce maintenance costs, and facilitate the transportation of genetic samples, the current method requires breakable, custom-made, and expensive glass ampoules. In the present study, we developed a simple and economical method for collecting freeze-dried (FD) sperm using commercially available plastic microtubes. Mouse epididymal sperm suspensions were placed in 1.5 ml polypropylene tubes, frozen in liquid nitrogen, and dried in an acrylic freeze-drying chamber, after which they were closed under a vacuum. The drying duration did not differ between the microtube and glass ampoule methods (control); however, the sperm recovery rate was higher using the microtube method, and the physical damage to the sperm after rehydration was also reduced. Intracytoplasmic sperm injection (ICSI) using FD sperm stored in microtubes at −30°C yielded healthy offspring without reducing the success rate, even after 9 months of storage. Air infiltration into all microtubes stored at room temperature (RT) within 2 weeks of storage caused a drastic decrease in the fertilization rate of FD sperm; underwater storage did not prevent air infiltration. RT storage of FD sperm in microtubes for 1 week resulted in healthy offspring after ICSI (5-18%), but the addition of silica gel or CaCl2 did not improve the success rate. Our novel microtube method is currently the simplest and most effective method for treating FD sperm, contributing to the development of alternative low-cost approaches for preserving and transporting genetic resources.